Source function and plane waves: Toward complete bader analysis - Tantardini, Christian; Ceresoli, Davide; Benassi, Enrico (Journal of computational chemistry, 2016)
The source function (SF) is a topological descriptor that was introduced and developed by C. Gatti and R.W. Bader in 1998. The SF describes the contribution of each atom to the total electron density at a given point. To date, this descriptor has only been calculable from electron densities generated by all‐electron (AE) methods for the investigation of single molecules or periodic systems. This study broadens the accessibility of the SF, offering its calculation from electron densities generated by plane wave (PW) methods. The new algorithm has been implemented in the open source code, CRITIC2. Our novel approach has been validated on a series of test systems, comparing the results obtained at PW level with those previously obtained through AE methods. © 2016 Wiley Periodicals, Inc. The Source Function (SF) is a topological tool based on Bader's Theory to describe the atomic contribution to the charge density. For the first time the SF calculation has been performed on plane wave Self Consistent Field (PWscf) charge densities. The algorithm has been implemented into open CRITIC2 code. Different test systems are used to evaluate the robustness of the algorithm. This work allows to perform complete Bader's analyses on crystals, surfaces, molecules using PWscf.